Market reaction to optimistic bias in the recommendations of chaebol-affiliated analysts. Issue 2 (August 2019) - Lim, Youngdeok; Kim, Hyungtae
Abstract: Using the setting of chaebol industrial organizations in Korea, which allows for the study of a unique affiliation between a chaebol group and financial analysts, we examine whether investors react to an optimistic bias in affiliated analysts' recommendations. Our initial market return tests, abnormal trading volume tests and independent analysts' reaction tests suggest that investors and independent analysts recognize and discount an optimistic bias in chaebol-affiliated 'buy' recommendations. However, long-term market returns are more profitable in terms of affiliated analysts' 'buy' recommendations than independent analysts' recommendations, which suggests that investors excessively discount chaebol-affiliated 'buy' recommendations in the short-term.